1971
DOI: 10.1136/hrt.33.4.540
|View full text |Cite
|
Sign up to set email alerts
|

Plasma digoxin concentrations and digoxin toxicity in hospital patients.

Abstract: Studies were made on io8 subjects on routine oral maintenance digoxin therapy. Twenty-two were found to have eidene of digoxin toxicity. The range of plasma digoxin concentrations in these subjects is recorded (1.38 SD+oO77 ng/ml). The subjects with evidence of toxicity are shown to have significantly higher plasma digoxin concentrations (3.36 SD I2o ng/ml) though there is some overlap with the non-toxic group. The subjects with toxicity are shown to be substantially older and to have a much higher incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
2

Year Published

1976
1976
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(16 citation statements)
references
References 12 publications
0
13
1
2
Order By: Relevance
“…Digoxin is one of the most prescribed drugs with advantages, including cost-effectiveness and well-tolerance, and the disadvantage of a mainly narrow therapeutic range [1],[3]. In studies performed in the 1970s, it was reported that 23% of patients on digoxin therapy were admitted to hospitals for digoxin intoxication [5]–[7]. Over the years digoxin intoxication rates reduced, as defined in Digitalis Investigation Group (DIG) study, and the hospitalization rate for digoxin intoxication was 2% [8]…”
Section: Discussionmentioning
confidence: 99%
“…Digoxin is one of the most prescribed drugs with advantages, including cost-effectiveness and well-tolerance, and the disadvantage of a mainly narrow therapeutic range [1],[3]. In studies performed in the 1970s, it was reported that 23% of patients on digoxin therapy were admitted to hospitals for digoxin intoxication [5]–[7]. Over the years digoxin intoxication rates reduced, as defined in Digitalis Investigation Group (DIG) study, and the hospitalization rate for digoxin intoxication was 2% [8]…”
Section: Discussionmentioning
confidence: 99%
“…Although digitalis toxicity is usually correlated with a high plasma concentration of the glycoside (Beller, Smith, Abelmann, Haber & Hood, 1971;Evered & Chapman, 1971;Carruthers, Kelly & MacDewitt, 1974), toxic effects may also occur in patients with normal therapeutic levels. This may be due to an increased myocardial sensitivity to the glycoside.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike digoxin, the elimination of digitoxin is unaffected by alterations in renal function (Storstein, 1974) and there are no problems with bioavailability after oral dosing (Beerman, Hellstrom & Rosen, 1971;Shaw, Howard & Hamer, 1972). In addition an overall incidence of toxicity of 5.8% for digitoxin (Storstein et al, 1977) is considerably lower than the 21% for digoxin found by Evered & Chapman (1971). Since digitalis therapy is invaluable in certain conditions such as fast atrial fibrillation which is present in 2.5% of the population over 60 years (Kitchin, Lowther & Milne, 1973) and digoxin use in the elderly is often unsatisfactory, digitoxin may be a preferable choice.…”
Section: The Effect Of Age On Digitoxin Pharmacokineticsmentioning
confidence: 99%